Neoliberal Education and the Redefinition of Democratic Practice in Chicago - Taylor, Kendall A. (New Frontiers in Education, Culture, and Politics, 2018)
The book uses Chicago as a case study to examine the cultural politics surrounding neoliberal education policy in general and the concomitant alterations to democratic practice in particular. After juxtaposing the numerous failures of neoliberal education policy and the language of democratic norms used by those who continually double-down on these same policies, it examines four distinct but related policy arenas. Each chapter begins with a vignette of a particular example of the neoliberal education policy in action. Taken together, Taylor illuminates the anti-democratic nature of neoliberal education policy and the toll it takes on democratic practice in urban space. The book concludes with a discussion of what resistance might look like in spaces which co-opt democratic concepts for anti-democratic ends.